Virtual Reality Systems of Media Technologies, Human-Machine Interactions, and France on the Road to Prevention - Diana Chankotadze (Research Parks Publishers, 2021)
The combination of human and machine is called the interaction of person and machine, or the world term HMI (human-machine interfaces) and more specifically its definition sounds like technical means and tools that man can control, create and manage. Specialized engineers have been studying for many years, in particular how humans interact with computers and computers, as well as developing systems, programs that are efficient, easy to use or generally adapted to the context of everyday use.